(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: N-methyl D aspartate receptor (NMDAR)-antibody encephalitis, is the most common form of autoimmune encephalitis in children, has now exceeded the incidence rate of infectious encephalitis according to the latest data in the United States and Europe. In southern Vietnam, particularly Ho Chi Minh City, we currently do not have much clinical data on this emerging disease. Therefore, we conducted this study to determine the clinical characteristics of NMDAR-antibody encephalitis at Children’s Hospital 1. Methods: Prospective observational study from March 2020 to December 2022 at Children’s Hospital 1. Results: NMDAR-antibody encephalitis was observed in 23 hospitalized children. The main clinical manifestations were mental symptoms (73.9%), cognitive disorders (69.6%), language changes (69.6%), abnormal movements (69.6%), and dyskinesia (65.2%). EEG was characterized by delta brush (13.0%) and slow waves (52.2%). Brain lesions on MRI recognized mainly in the limbic system (65.2%), thalamus (39.1%), midbrain (39.1%), and cerebellum (30.4%). Treatment included intravenous methylprednisolone (91.3%), immunoglobulin (39.1%), cyclophosphamide (30.4%), and rituximab (17.4%). Median hospital stay was 38 days. There was one case (4.3%) of death. There was no considerable clinical difference between encephalitis with positive and negative NMDAR-antibody. Conclusion: NMDAR-antibody encephalitis has been an emerging disease with an increasing number of new cases. Early immunotherapy when NMDAR-antibody encephalitis is suspected should be of consideration.